2016
DOI: 10.1177/0734242x15622812
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic solar panels of crystalline silicon: Characterization and separation

Abstract: Photovoltaic panels have a limited lifespan and estimates show large amounts of solar modules will be discarded as electronic waste in a near future. In order to retrieve important raw materials, reduce production costs and environmental impacts, recycling such devices is important. Initially, this article investigates which silicon photovoltaic module's components are recyclable through their characterization using X-ray fluorescence, X-ray diffraction, energy dispersion spectroscopy and atomic absorption spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 14 publications
2
27
0
1
Order By: Relevance
“…Due to the strong bonding capability of the EVA encapsulant in the solar cell, it was impossible to separate the layers cleanly at room temperature and so, a well-controlled thermal process was used. The thermogravimetric analysis (TGA) results of the decomposition of EVA and the PV backsheets confirmed that the thermal process employed did not exceed or operate near decomposition temperatures so as not to alter the overall structure of the EVA and backsheet layers 65,66 . Following extensive testing, it was determined that the solar cells were to be added to a genlab oven for 10 minutes at 190 °C for optimum results in removing the polymeric material by softening some of the polymers in the laminate structure.…”
Section: Methodsmentioning
confidence: 82%
“…Due to the strong bonding capability of the EVA encapsulant in the solar cell, it was impossible to separate the layers cleanly at room temperature and so, a well-controlled thermal process was used. The thermogravimetric analysis (TGA) results of the decomposition of EVA and the PV backsheets confirmed that the thermal process employed did not exceed or operate near decomposition temperatures so as not to alter the overall structure of the EVA and backsheet layers 65,66 . Following extensive testing, it was determined that the solar cells were to be added to a genlab oven for 10 minutes at 190 °C for optimum results in removing the polymeric material by softening some of the polymers in the laminate structure.…”
Section: Methodsmentioning
confidence: 82%
“…The X-rays diffraction and fluorescence analysis have been used to identify the components of photovoltaic modules made with silicon cells 1,2 . Figure 3 shows the X-rays diffractograms for samples with and without antireflection layer, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the photovoltaic technologies, the silicon semiconductor has dominance on the market; however, its limited lifetime means that silicon photovoltaic modules will become electronic waste 1 . The recycling of photovoltaic modules is important for the recovery of materials, reduction of costs and environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…conventional resources such as glass, Al, plastic, as well as valuable metals (Ag, In, Ga, Te, etc. ), whereas the latter have been recently determined to be at near-critical supply risk (Dias et al, 2016a). Instead, sound recycling processes can play a key role in protecting the environment by reducing the risks pertinent to hazardous substances such as toxic metals, poly/brominated flame retardants, etc.…”
Section: Context and Motivationmentioning
confidence: 99%